Mandatory use of confirmation stage with Chlamydiazyme during urinary sediment analysis. Issue 10 (October 1993) - Anderson, J R; Mumtaz, G; Mulhare, P; Poddar, J; Ridgway, G L
Abstract : AIMS--To assess whether false positive results found when the first stage Chlamydiazyme test is performed on urinary sediment could be reduced by using the more specific second stage blocking assay. METHODS--Sediment from 173 urine samples from patients with suspected urinary tract infection caused by Gram negative bacteria and 23 control urine samples were tested using the Chlamydiazyme assay system, which included a blocking assay. RESULTS--A reaction result with the first stage Chlamydiazyme assay test was seen in 102 (58.9%) of the test urine samples. First stage reactivity was not blocked by the Chlamydiazyme confirmatory assay performed on repeat testing. All were correctly identified as true negative (first test false positive) results. CONCLUSIONS--Use of a second (specific) blocking assay for the analysis of urinary sediment using Chlamydiazyme eliminates false positive results in Gram negative urinary tract infections.